PERANCANGAN RUMAH SAKIT PARU DI DENPASAR - I Gede Indra Kamiana Putra; Ida Bagus Idedhyana; Ayu Putu Utari Parthami Lestari (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2023)
Pulmonary Special Hospital is a hospital that provides health services based on pulmonary special disciplines and special medical treatment for pulmonary organs with disabilities, sleep disorders, and allergies. The number of lung disease sufferers in Bali Province has increased after Covid-19. Currently, the Province of Bali does not yet have special treatment and healing facilities for lung diseases. Handling of lung disease is still handled by public hospitals, both government and private, operating in Bali. Lung disease patients need adequate facilities and infrastructure and good building circulation. Thus, it is necessary to procure large-scale public health facilities in the form of a Lung Hospital, a class A special hospital that accommodates patients with lung disease in the Province of Bali. The design method used is the data collection technique in the form of literature studies, observation, and comparative studies, as well as data processing methods namely methods of analysis, synthesis, and transformation. The results of the design of the Lung Hospital in Denpasar refer to the basic concept of Healing Architecture with an architectural theme, namely Green Architecture. Green Architecture is applied to the use of parks and lung hospital technology.